Student project teams : great idea - wrong species? - Stevenson, Barry J (School of Education, 2014)
This research dissertation presents the findings of an investigation of the literature into the question of whether the use of student project teams helps create a more effeetive learning environment for the development of the sort of skills referred to above or are they, as Argyris suggests, helping reinforce model 1 'theories-in-use'such as ""skilled incompetence and defensive reasoning"", of both educators and learners alike?